Smart Home Berbasis Internet of Things (IoT) Dalam Mengendalikan dan Monitoring Keamanan Rumah - Supiyandi Supiyandi; Chairul Rizal; Muhammad Iqbal; Muhammad Noor Hasan Siregar; Muhammad Eka (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Smart Home or smart home is a system built with the help of a computer to integrate and control home devices automatically and efficiently. The development of